Pemanfaatan Minyak Biji Bunga Matahari (Helianthus annuus L.) pada Formulasi Nanokrim dan Evaluasi Fisik Sediaan - Sri Fitrianingsih; Setiani, Elisa Dyah; Pratiwi, Yulia; Hidayati, Rakhmi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Sunflower plants (Helianthus annuus L.) are annual plants from the Asteraceae family. This plant is cultivated as an oil producing plant. Sunflower seed oil is an excellent source of vitamin E. This vitamin is highly fat-soluble and contains flavonoid antioxidants, which prevent skin cell damage due to free radicals and help hydrate and regenerate skin cells. Nanocream is a nanoemulsion or o/w or o/m colloidal dispersion in semisolid form and consists of an oil phase dispersed into a water phase or vice versa forming droplets with a diameter of 10-100 nm. This research aims to determine the formulation and physical evaluation of sunflower seed oil nanocream (Helianthus annuus L.). The nanocream preparation was formulated into 4 formulations, namely with concentrations of 2.5%, 5% and 7.5%. The characteristics of the physical properties of nanocream include organoleptic test, homogeneity test, pH test, adhesion test, spreadability test, cream type test and viscosity test. The research results showed that the nanocream formulation had a pH value of 8.30-8.86, in the adhesion test it had a value of 4.7-11.04 seconds. In the test the spreadability of the nanocream preparation formulation had a value of 3.8-5.1 cm, in the cream type test the sunflower seed oil nanocream formulation made had the oil-in- water (O/W) emulsion type and in the viscosity test the nanocream made had the value 3.8-5.1 cm. formulation has a value of 3336.6-5455.2 cPs. There is the best nanocream preparation formulation that meets the physical characteristics of nanocream, namely F3.